2018
DOI: 10.3390/catal8080303
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Catalytic Mineralization of Toluene Adsorbed on CeO2

Abstract: Abstract:In the context of coupling nonthermal plasmas with catalytic materials, CeO 2 is used as adsorbent for toluene and combined with plasma for toluene oxidation. Two configurations are addressed for the regeneration of toluene saturated CeO 2 : (i) in plasma-catalysis (IPC); and (ii) post plasma-catalysis (PPC). As an advanced oxidation technique, the performances of toluene mineralization by the plasma-catalytic systems are evaluated and compared through the formation of CO 2 . First, the adsorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…ozone [5][6][7]. The conversion, energy efficiency, carbon balance and selectivity to CO 2 are improved when plasma is coupled with a catalyst and undesired by-products such as ozone and solid deposits at walls are suppressed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…ozone [5][6][7]. The conversion, energy efficiency, carbon balance and selectivity to CO 2 are improved when plasma is coupled with a catalyst and undesired by-products such as ozone and solid deposits at walls are suppressed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al synthesized a novel photocatalyst and combined it with dielectric barrier discharge (DBD) plasma to remove isopropanol (IPA) [25]. Jia et al studied the mineralization of toluene using nonthermal plasma combined with CeO 2 as an adsorbent and found that the amount of ozone produced by the discharge plays a key role in the mineralization process [26]. The combination of plasma with nanomaterials could improve the generation of reactive species and the reaction area and increase the selectivity of the degradation process [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al investigated toluene oxidation with CeO 2 as an adsorbent and they compared in-plasma catalysis (IPC) and post-plasma catalysis (PPC) [15]. The total, reversible and irreversible adsorbed fractions were quantified.…”
mentioning
confidence: 99%